Effects of Soil Type on the Damage Potential of Meloidogyne incognita on Soybean - Windham, G L (Journal of nematology, 1986)
Effects of soil type on the reproduction and damage potential of Meloidogyne incognita on soybean, Glycine max (L.) Merr., were determined at five locations in North Carolina, including one site where plots with six soil types were established. M. incognita reproduced readily on a susceptible soybean cultivar in most soil types, with somewhat limited reproduction in muck soils. The relationship between initial population densities and yield varied among soil types and nematode populations. Yield losses were greatest in sandy and muck soil types, with less nematode damage occurring in the clay soil types. A North Carolina and a Georgia population of M. incognita differed greatly in their ability to reproduce on soybean and suppress growth. The North Carolina population had a moderate effect on yield in 1981 and only a slight effect in 1982. In contrast, a Georgia population severely limited soybean growth and yield at lower initial population densities in 1983, Initial population densities of the nematodes and physical and chemical edaphic factors accounted for much of the variation of soybean yield and nematode reproduction